THE EFFECTIVENESS OF ZUMBA KIDS IMPLEMENTATION INTO PHYSICAL EDUCATION OF ELEMENTARY SCHOOL PUPILS - Rymar, Olga; Sorokolit, Nataliya; Solovey, Alla; Yaroshyk, Marta; Khanikiants, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The demand to improve physical education process of elementary school pupils by the tools of innovative dancing fitness branch – Zumba Kids is described in the article. Positive changes in dynamics among children have occurred in indicators of functional and physical preparation in conditions of the experiment. The goal of the work is the optimization process of physical education of elementary school pupils by Zumba Kids tools. There were investigated children’s physical development, functional and physical preparation and experimentally was checked the effectiveness of the implementation program of Zumba Kids tolls into process of physical education. There were 54 participants, 26 among them are boys and 28 are girls (the children’s age is 9 years old). The methods of the research are theoretical analysis and literature sources generalization; physiological research methods; pedagogical observation (passing of control standards); pedagogical experiment and mathematical statistics methods. There are presented and scientifically justified the program of implementing Zumba Kids tools into physical education lessons of elementary school pupils. The content of the program consists of the synthesis of energetic modern dances with aerobics, fitness exercises, stretching and also exercises for breathing exercises and muscle relaxation. The elaborated program is realized in the educational process and proved its effectiveness. The results of investigation have shown its positive influence on the functional and physical preparation of elementary school pupils. It was proved by mathematical statistics methods.